VLSI Design for Low Power Home Automation and Security System Controller - Ngieng, Bryna Sing Yii; Ahmad, Nornabihah (Evolution in Electrical and Electronic Engineering, 2021)
The home automation system results from the rise of the automation era, which promotes the quality of living and energy resources savings. The current popularity of the home automation system is low as it hindered by its system complexity, complex user interface, power consumption, costing, absence of a security system and no backup power. Thus, this study aims to develop a compact home automation and security system controller consisting of environment comfort control, security system, and automatic load transfer switch system to archive a low power consumption. Very Large-Scale Integration (VLSI) design processes such as front-end and back-end were used for this project design via Synopsys EDA tools. At the same time, careful analysis of the performance and constraints were done to ensure no timing violations and physical design violations. The final layout's total power consumption was successfully lowered from the front-end design to 65.61μW. A positive timing slack of 1.95ns is obtained for the final layout of the design. Meanwhile, the final layout's dynamic power and leakage power is lowered by 4.67μW and 0.31μW, respectively, compared to the front-end process. The proposed design is successfully designed in low power and all the system functioned correctly concerning the input stimuli given under 100MHz.